The first Asian record of the mouse-deer Afrotragulus (Ruminantia, Tragulidae) reassess its evolutionary history and offers insights on the influence of body size on Afrotragulus diversification. (3rd August 2022) - Sánchez, Israel M.; Abbas, Sayyed Ghyour; Khan, Muhammad Akbar; Babar, Muhammad Adeeb; Quiralte, Victoria; DeMiguel, Daniel
ABSTRACT: New fossils of the Miocene crown-tragulid Afrotragulus from Chinji and Dhok Pathan Formations of the Pakistan Siwaliks Group represent its first record out of Africa. This material from Babri Wala (ca. 12.6 Ma), Hasnot 6 (ca. 6.5 Ma) and Barnum Brown's B 51 classic locality (ca. 13.7 Ma) constitutes three new species, Afrotragulus akhtari, A. moralesi and A. megalomilos . We reassess Afrotragulus ingroup phylogeny recovering two clades with African and Asian representatives. Our results reject the existence of a strictly African lineage in the genus. Body-size estimates show three tiny Afrotragulus with a size corresponding to the lower spectrum of extant Tragulus . However, both Afrotragulus lineages produced species larger than 10 kg. Previously considered very small tragulids, these new forms demonstrate that size range of Afrotragulus equals that of all living tragulids. The smallest forms could be frugivorous/browsers but A. megalomilos and A. moralesi could be opportunistic feeders, specially accounting for their highly derived dentition. These new Asian Afrotragulus extend the biochronological range of the genus from the lower Miocene to the late upper Miocene. Afrotragulus is surprisingly uncovered here as one of the longest-lived and most successful members of the Tragulidae, existing during ca. 13.5 million years (20–6.5 Ma).